2021
DOI: 10.1016/s1474-4422(20)30432-4
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric multiple sclerosis and antibody-associated demyelination: clinical, imaging, and biological considerations for diagnosis and care

Abstract: The field of acquired central nervous system neuroimmune demyelination in children is transforming. Recent advances in assay development, refinement of diagnostic criteria, increased biological insights provided by advanced neuroimaging techniques, and level 1A evidence for therapeutic efficacy of biological agents are re-defining diagnosis and care. Three distinct neuroimmune conditions-multiple sclerosis (MS), anti-myelin oligodendrocyte glycoprotein antibody associated disease (MOGAD) and anti-aquaporin-4 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
70
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 75 publications
(72 citation statements)
references
References 116 publications
2
70
0
Order By: Relevance
“…An event of acquired CNS demyelination in children younger than 18 years old, also known as acquired demyelinating syndrome (ADS), could represent one of many neuroinflammatory diseases including AQP4-NMOSD, MOGSD, acute disseminated encephalomyelitis (ADEM) with encephalopathy, or a monophasic disease [ 14 ]. In fact, only 20% of pediatric ADS cases are ultimately diagnosed with POMS [ 15 ].…”
Section: Diagnosis Of Poms and Differential Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…An event of acquired CNS demyelination in children younger than 18 years old, also known as acquired demyelinating syndrome (ADS), could represent one of many neuroinflammatory diseases including AQP4-NMOSD, MOGSD, acute disseminated encephalomyelitis (ADEM) with encephalopathy, or a monophasic disease [ 14 ]. In fact, only 20% of pediatric ADS cases are ultimately diagnosed with POMS [ 15 ].…”
Section: Diagnosis Of Poms and Differential Diagnosismentioning
confidence: 99%
“… Table modified from Fadda et al [ 14 ] ADEM acute disseminated encephalomyelitis, AQP4-NMOSD aquaporin-4 neuromyelitis optica spectrum disorder, CSF cerebrospinal fluid, F:M female:male, LETM longitudinal extensive transverse myelitis, MOGSD myelin oligodendrocyte glycoprotein antibody spectrum disorder, MS multiple sclerosis, OCB oligoclonal bands, ON optic neuritis, POMS pediatric-onset multiple sclerosis …”
Section: Diagnosis Of Poms and Differential Diagnosismentioning
confidence: 99%
“…Compared with individual factors, this risk score model exhibited better performance to differentiate the children with relapse in the cohort. Actually, several of these 4 factors have been reported to be associated with clinical relapse; for example, maintenance therapies like AZA, MMF, and rituximab treatment have been demonstrated to decrease the risk of relapse and disability for pediatric patients with NMOSDs (6,12,19,33), and the increase in the risk of relapse was observed frequently in the patients starting with ADEM plus ON/TM (mixed lesion) (34).…”
Section: Discussionmentioning
confidence: 99%
“…Pediatric NMOSDs commonly manifest as recurrent attacks of variable symptoms if untreated and have a high risk of permanent visual and motor deficit due to the stepwise accumulation of disability (12). Hence, the accurate prediction of relapse and the early attack-preventing treatment are crucial for clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The results substantiated that mice exposed to BCAS plus CRS exhibited severe anxiety and depression-like behavior due to myelin loss in vHIP, that could be partially mitigated with application of Quercetin, indicating that Quercetin turnovers the loss of mature oligodendrocytes and might potentiate the regenerative ability of OPCs, in a degree. Previous studies have demonstrated that cerebral hypoperfusion is one of the most common pathophysiological mechanism, which is a main cause to cognitive decline and neuropsychiatric symptoms progression in AD and VaD [43][44][45]42]. However, unlike AD, there are no pharmacological treatments for VaD-associated neuropsychiatric symptoms.…”
Section: Discussionmentioning
confidence: 99%